PENGETAHUAN AKUNTANSI DAN KARAKTER KEPEMIMPINAN TERHADAP KINERJA MANAJERIAL - Wibowo, Agung Edy; Cahayani, Kartika; Silitonga, Frangky; Supratman, Supratman; L. Tobing, Vargo Christian (LPPM Universitas Putera Batam, 2025)
In today's complex business environment, a robust understanding of accounting is paramount, serving as the bedrock for sound financial health, strategic decision-making, regulatory compliance, and comprehensive performance evaluation. This essential knowledge allows organizations to accurately track income and expenditures, manage cash flow effectively, and ensure transparency for stakeholders. Building upon this foundation, strong and transformative leadership significantly amplifies managerial performance by inspiring teams to transcend ordinary expectations, fostering a culture of innovation, and aligning individual efforts with overarching organizational visions. Such leaders empower their workforce, encourage critical thinking and ethical behavior, and develop strong interpersonal relationships, which collectively cultivate higher levels of employee commitment, job satisfaction, and ultimately, superior operational and strategic outcomes. The test results, using a convenience sampling method with 51 respondents, indicate that: accounting knowledge alone does not have a significant influence on managerial performance, however, this knowledge significantly affects transformative leadership character. This study also found that leadership character has a significant influence on managerial performance. Furthermore, it was found that leadership character significantly mediates the influence of accounting knowledge on managerial performance